2018
DOI: 10.1038/s41567-018-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-transport controlled by Landau polariton states

Abstract: Hybrid excitations, called polaritons, emerge in systems with strong light-matter coupling. Usually, they dominate the linear and nonlinear optical properties with applications in quantum optics. Here, we show the crucial role of the electronic component of polaritons in the magnetotransport of a cavity-embedded 2D electron gas in the ultrastrong coupling regime. We show that the linear dc resistivity is significantly modified by the coupling to the cavity even without external irradiation. Our observations co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 39 publications
7
134
0
Order By: Relevance
“…where -H D P is defined in equation (19). Combining equations (B1)-(B3) shows that the expression forˆ(…”
Section: Appendix a Isotropic Heisenberg Modelmentioning
confidence: 94%
See 3 more Smart Citations
“…where -H D P is defined in equation (19). Combining equations (B1)-(B3) shows that the expression forˆ(…”
Section: Appendix a Isotropic Heisenberg Modelmentioning
confidence: 94%
“…The resonant electron-photon coupling described by -H D P in equation (19) results in the formation of doublon-photon polaritons. All eigenstates of -H D P with non-zero eigenvalues can be constructed from the eigenstates ofĤ S with non-zero eigenvalues (see appendix C).…”
Section: Mott Polaritonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent transport experiments in cavity-embedded organic semiconductors [10,11] and in-plane magnetotransport measurements in cavity-embedded high-mobility two-dimensional electron systems [12] have shown that the linear-regime electronic conductance of a material can be significantly affected by a cavity electromagnetic resonator even in the absence of illumination. Early theoretical works exploring the role of a cavity on transport have focused on cavity-modified excitonic linear transport [13,14] and charge nonlinear conduction [15] for chains of two-level systems in the nonlinear regime where electrons are injected in the excited levels.…”
Section: Introductionmentioning
confidence: 99%